Letter : Assistance for Spain - Fernández-Shaw, Daniel
030-0062-001 SPANISH EMBASSY, COMMERCIAL OFFICE. 21, CAVENDISH SQUARE, LONDON, W.1. TELEPHONE, LANGHAM 3671 TELEGRAMS:"OFCOMES" LONDON. G.S. Your ref: WMC/HVT/CB 15th. September 1938. Sir Walter Citrine K.B.E., Trades Union Congress, Transport House, Smith Square, London S.W.1. Dear Sir Walter, Assistance for Spain I have the pleasure to ackknowledge receipt of your letter on the above subject which has been read with interest and for which I thank you. I am pleased to note that Mr.Tewson will maintain contact with this office. Yours sincerely, D F Shaw Daniel Fernández-Shaw. EAB 292/946/30/62